Case Report: Unique case of lens replacement in high hyperopia with trifocal lens and piggyback light-adjustable lens implantation - Shafiee, Amirmohammad; Ali, Arsalan A.; Gadicherla, Anirudh; Nasser, Taj (Frontiers in Ophthalmology, 2025)
Managing high hyperopia is notably challenging due to the unpredictability of refractive outcomes. Moreover, the technical difficulties of surgery in patients with smaller eyes, compounded by the limitations in available intraocular lens (IOL) powers in the United States, necessitate innovative approaches to achieve emmetropia. This case report discusses a novel approach using a light-adjustable lens (LAL) with a trifocal IOL to address these complexities and achieve spectacle independence. A 36-year-old man, who works as a military aircraft inspector and has high hyperopia and a history of left eye (OS) strabismic amblyopia, sought freedom from spectacles due to occupational demands. Pre-operative assessment showed severe uncorrected visual acuity and short axial lengths. Refractive lens exchange was performed bilaterally, utilizing a trifocal IOL combined with a light-adjustable lens OD and a high-powered monofocal lens OS. Post-operatively, significant improvement in visual acuity was observed, with heightened patient satisfaction. This case demonstrates the effectiveness of integrating a light-adjustable lens with a trifocal IOL to address high hyperopia in a less invasive manner and foster spectacle independence with patient satisfaction. Our approach offers promising implications for refractive surgery, highlighting the potential for tailored solutions in complex cases.